2020
DOI: 10.1186/s12882-020-01888-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the role of eculizumab in systemic lupus erythematosus-associated thrombotic microangiopathy

Abstract: Background: Lupus nephritis (LN) is a severe consequence of systemic lupus erythematosus (SLE) that affects approximately 40% of patients. Pathogenic immune complexes that are characteristic of LN deposit in the kidney and activate immune mediated pathways including the complement system. Complete remission rates in LN are approximately 44% highlighting the need for new treatment strategies in these patients. Eculizumab is a fully humanised IgG2/IgG4 monoclonal antibody directed at C5 and thus prevents the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 42 publications
(46 reference statements)
0
37
0
3
Order By: Relevance
“…A majority (28/30) of the patients had resolution of symptoms and recovery of renal function or were able to be discharged from the hospital. This underscores the interest in the development of complement inhibitory medications and the need for markers to determine which patients will benefit the most from them [ 34 •].…”
Section: Complement Activation With Other Lupus Featuresmentioning
confidence: 99%
“…A majority (28/30) of the patients had resolution of symptoms and recovery of renal function or were able to be discharged from the hospital. This underscores the interest in the development of complement inhibitory medications and the need for markers to determine which patients will benefit the most from them [ 34 •].…”
Section: Complement Activation With Other Lupus Featuresmentioning
confidence: 99%
“…Targeting the activated complement system with complement inhibitors may also promote GC-reduced or GC-free regimens. Although complement inhibition in lupus nephritis has been used in a few case reports ( 96 , 97 ), particularly in the context of concomitant thrombotic microangiopathy, the CLEAR ( 98 ) and ADVOCATE ( 99 ) studies in ANCA-associated vasculitis suggest this may be an approach worth investigating in lupus nephritis. In these studies, administration of avacopan (an oral complement C5aR inhibitor) along with cyclophosphamide or rituximab, allowed the administration of a GC-free regimen with higher remission rates at 52 weeks of follow-up in patients with ANCA-associated vasculitis ( 99 ).…”
Section: Schemes Free Of Oral Glucocorticoidsmentioning
confidence: 99%
“…Recently, a case series has shown that eculizumab results to favourable outcomes in patients with aHUS and SLE [ 7 , 11 , 16 ]. Eculizumab led to improvement of symptoms, thrombocytopaenia, kidney function, and proteinuria in patients who were refractory to conventional immunosuppressive treatment and plasmapheresis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%